2015
DOI: 10.1007/s10384-015-0398-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in filtering bleb morphology after bleb-related infection

Abstract: This study revealed that the filtering bleb became smaller, both tangentially and circumferentially, and thicker, after stage III infections than after stage I or II infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several studies have reported that filtering bleb infection may occur after anti-glaucoma surgery[ 4 , 5 ]. Intraocular inflammation has been observed in some severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that filtering bleb infection may occur after anti-glaucoma surgery[ 4 , 5 ]. Intraocular inflammation has been observed in some severe cases.…”
Section: Discussionmentioning
confidence: 99%